'Cheap Talk'? Second screening and the irrelevance of TV political debates. (August 2019) - Ceron, Andrea; Splendore, Sergio
This article analyzes 3 months of online debate during the electoral campaign for the 2016 Italian constitutional referendum. Through supervised sentiment analysis, we assess the extent of support for the referendum within the general public of Twitter users ( Twittersphere ) by analyzing the voting intentions expressed online in 2, 369, 333 tweets. Similarly, we exploit the practice of social TV and investigate the support for the referendum expressed by the 160, 465 tweets posted by second screeners, that is, the subsample of Twitter users who watched and actively commented on nine political talk shows during the campaign. We compare the mentions and the attitudes of the Twittersphere and the second screeners by means of a lead–lag analysis to test whether the second screeners can act as influencers and trendsetters able to shape or anticipate attention and opinions toward an issue within larger audiences. The results reveal an inverse relationship between the Twittersphere and the second screeners whereby the reactions of the latter diverge from those of the general Twitter public. This finding has implications for the literature on echo chambers and the polarization of social media.